2016
DOI: 10.1108/ejm-07-2015-0510
|View full text |Cite
|
Sign up to set email alerts
|

Beauty blogger selfies as authenticating practices

Abstract: Purpose The purpose of this paper is to consider the use of beauty blogging selfies in conveying consumer authenticity. The authors used an under-researched consumer-based authenticity approach. Design/methodology/approach The authors adopt a practice theory approach to selfies as both objects and practices. The study combines depth-interviews with a review of the participants’ blogs and selfies. Findings This research shows that bloggers use selfies as records of product trial, success and failure via spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 33 publications
1
49
0
3
Order By: Relevance
“…Our study also concluded and measured the selfie-posting behavior of Indians; findings revealed that women are more interested and active to post selfies on social media platforms. Our result supports the previous literature and contributes to an understanding of posting selfies as practices in the context of theory (Albury 2014;Gannon and Prothero 2016;Kedzior et al 2016).…”
Section: Discussion Of Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Our study also concluded and measured the selfie-posting behavior of Indians; findings revealed that women are more interested and active to post selfies on social media platforms. Our result supports the previous literature and contributes to an understanding of posting selfies as practices in the context of theory (Albury 2014;Gannon and Prothero 2016;Kedzior et al 2016).…”
Section: Discussion Of Resultssupporting
confidence: 91%
“…While most of the previous studies have shown that women are more engaged in selfie posting behavior and have shown the traits of the social exhibition and self-esteem, our results are contrary to this as Indian men exhibit more social exhibition than women. Indian men display and show themselves off much more than women; perhaps connected with a need to be the center of attraction and attention (Gannon and Prothero 2016). The results may also be correlated with the patriarchal structures prevalent in Indian society.…”
Section: Effect Of Gender On Various Factors Influencing Selfie-postimentioning
confidence: 85%
“…blogs (Gannon and Prothero, 2016). However, netnography is not limited to textual online data, and many netnographic marketing studies also include pictures and videos.…”
Section: Content Includedmentioning
confidence: 99%
“…Facebook) have contributed to the widespread adoption of the "snapshot" style, a straightforward, generally unposed photograph of everyday life (Schroeder, 2012). A key aspect of the snapshot style is its "authentic" look, which derives from randomness and spontaneity through which visual elements are portrayed in photographs (Gannon and Prothero, 2016). Cultivation theorists (Lobinger and Brantner, 2015) would argue that frequent exposure to snapshot-like imagery leads viewers to interpret the portrayed action in visualised narratives as an authentic act.…”
Section: The Photographic Style: Snapshot Versus "Parody" Selfiementioning
confidence: 99%
“…Thus far, although exceptions exist (Gannon and Prothero, 2016;Pounders et al, 2016), scholars have paid scant attention to the influence of consumer photos. Marketing research in the domain of personal photography has mainly highlighted its representational role, namely the depiction of consumer life stories for consumer identity formation and maintenance (Holt, 1995).…”
Section: Introductionmentioning
confidence: 99%